2022
DOI: 10.1039/d1tb02820k
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular J-aggregates of aza-BODIPY by steric and π–π nteractions for NIR-II phototheranostics

Abstract: Achieving J-aggregation of a molecule is a fascinating way to construct fluorescent imaging as well as photothermal therapy agents in the second near-infrared window. Modulation of the balance between intermolecular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…Moreover, the loading capacity of aza-BODIPY-mPEG was calculated to be 54 ± 9%, according to the % yield of the conjugate. The NPs showed NIR absorbance peaking at 842 nm with a 15 nm bathochromic shift compared with that of aza-BODIPY-A in DMSO, which is possibly attributed to the interaction of strong π–π stacking of aza-BODIPY molecules in the J -aggregation . However, these dye-based NPs did not exhibit any fluorescent signal, confirming nonradiative relaxation via photothermal effect (Figure S5).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, the loading capacity of aza-BODIPY-mPEG was calculated to be 54 ± 9%, according to the % yield of the conjugate. The NPs showed NIR absorbance peaking at 842 nm with a 15 nm bathochromic shift compared with that of aza-BODIPY-A in DMSO, which is possibly attributed to the interaction of strong π–π stacking of aza-BODIPY molecules in the J -aggregation . However, these dye-based NPs did not exhibit any fluorescent signal, confirming nonradiative relaxation via photothermal effect (Figure S5).…”
Section: Resultsmentioning
confidence: 89%
“…The NPs showed NIR absorbance peaking at 842 nm with a 15 nm bathochromic shift compared with that of aza- BODIPY-A in DMSO, which is possibly attributed to the interaction of strong π−π stacking of aza-BODIPY molecules in the J-aggregation. 39 However, these dye-based NPs did not exhibit any fluorescent signal, confirming nonradiative relaxation via photothermal effect (Figure S5). This PTT phenomenon might occur due to the intramolecular charge transfer from an electron-donating group such as NMe 2 and NH 2 groups to the aza-BODIPY core acting as the electron-accepting part.…”
Section: Photophysical Properties Of Aza-bodipy Npsmentioning
confidence: 78%
“…In recent years, some research groups reported NBA-OPDs with a response wavelength above 700 nm by taking advantage of the red shift of thin-film absorption caused by the J-aggregation properties of organic dye molecules. Based on this strategy, we screened some known organic dyes with J-aggregation properties, such as cyanine dyes, squaraine dyes, perylene dyes, metalloporphyrin dyes, aza-BODIPY dyes, merocyanine dyes, and PPCy dyes. These molecules have the characteristics of the large conjugated and planar structure and strong intermolecular non-covalent bonds, thus leading to strong coupling between molecules in the aggregated state, which in turn results in absorption narrowing and red shift and enhancement of the carrier transport rate via two-dimensional percolation pathways for electrons and hole charge carriers . Thus, these unique properties are desirable for the fabrication of NBA-OPDs.…”
Section: Introductionmentioning
confidence: 99%
“…21,23,24 Aza-BODIPY probes have exhibited attractive properties, in terms of facile synthesis and chemical modifications, outstanding optical properties and excellent photostability. [25][26][27][28] However, few of them exhibit NIR-II emission capabilities. [29][30][31][32] Herein, we report the design and preparation of a new aza-BODIPY-derived agent named CB1 with extended π-conjugation and proper structural modifications (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%